Metal roof cladding system under wind loading: State-of-the-art - Tiwari, Shubham; Roy, Krishanu; Fang, Zhiyuan; Lim, James B.P. (Journal of wind engineering and industrial aerodynamics, 2025)
Roof cladding, a vital component of any structure, is fabricated from material that is durable, affordable, and weatherproof. Metal roof claddings, known for their lightweight nature, durability, cost-effectiveness in construction and maintenance, and impressive strength-to-weight ratio, have been widely adopted worldwide. However, despite these advantages, metal roof claddings are particularly prone to failure during extreme wind events, such as storms, cyclones, and hurricanes. The two primary categories of metal roof claddings are long-run profiles and tray profiles. This study conducts a comprehensive review of research focused on standards used for quantifying wind loadings on roof structures, as well as the wind resistance capacity of various profiles of metal roof claddings under wind uplift loading. The review encompasses both experimental and numerical studies, exploring test methods, numerical modeling techniques, and modes of failures associated with different roof cladding profiles under wind uplift loading conditions. Additionally, the paper examines studies related to fragility and vulnerability analysis, along with risk assessment, pertaining to metal roof claddings. In conclusion, the paper offers critical remarks and provides recommendations for future work based on identified research gaps. The aim is to guide future studies in addressing challenges related to the wind performance of metal roof claddings and contribute to the development of more resilient and secure roofing systems.